Age Groups and Generations: Lines of Conflict and Potentials for Integration - Martin Kohli (Intergenerational Justice Review)
At the beginning of the 21st century, the old 'social question' – the integration of the industrial workers – seems to have been resolved, but new cleavages appear, for example between generations. These emerge from historical or macro-structural changes but also from economic cleavages between generations. The reason why age conflicts are not more pronounced is the mediating function of political parties, unions and families. Furthermore, although it is often claimed that the welfare state is increasingly dominated by the elderly, this is far from being the case. In terms of economic well-being, both the young and the old fare worse than the middle age group. In terms of political decision-making, there is no evidence for an alleged movement towards gerontocracy.